A truthful mechanism for crowdsourcing-based tourist spot detection in smart cities. (20th August 2022) - Chowdhury, Anil Bikash; Singh, Vikash Kumar; Mukhopadhyay, Sajal; Kumar, Abhishek; Dhananjaya, Meghana M.
With the advent of new technologies and the internet around the globe, many cities in different countries are involving the local residents (or city dwellers) for making decisions in various government policies and projects. In this paper, the problem of detecting tourist spots in a city with the help of city dwellers, in strategic setting, is addressed. The city dwellers vote against the different locations that may act as a potential candidate for the tourist spot. For the purpose of voting, the concept of single peaked preferences is utilised, where each city dweller reports a privately held single peaked value that signifies the location in a city. Given the above discussed scenario, the goal is to determine the location in the city as a tourist spot. For this purpose, we have designed the mechanisms (one of which is truthful). For measuring the efficacy of the proposed mechanisms the simulations are done.